The Gadamerian discourse in China and the fusion of aesthetic realms - Rošker, Jana S. (Asian studies, 2023)
Based on comparative philosophical methodology, this paper presents a new hermeneutic method for interpreting Chinese (especially ancient Chinese) texts. It first introduces the rich tradition of Chinese hermeneutics and then analyses its possible dialogues with European hermeneutic methods, especially Gadamer’s “fusion of horizons”. It identifies some methodological problems inherent in this method and, on this basis, proposes the application of a new hermeneutic method that may be more suitable for the interpreta-tion of traditional Chinese metaphysical and literary texts. It is based on the tradition-al philosophical-aesthetic notion of jingjie??. The author preliminarily refers to this method as a “fusion of aesthetic realms”.
Keywords: estetska sfera; fusion of aesthetic realms; fusion of horizons; Gadamer; hermeneutics; hermenevtika; jingjie; transcultural hermeneutics; transkulturna hermenevtika; Zhuangzi; zlitje estetskih sfer; zlitje obzorij